The Implementation of Differentiated Learning on Early Islamic Kindergarten in Lamongan, Indonesia - Uswatun Chasanah; Mohammad Syaifuddin; Ria Arista Asih (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2025)
This research aims to explore the planning, implementation, and assessment of differentiated learning for early Islamic kindergartens in Lamongan, Indonesia. The research method used is qualitative descriptive, with data collection through interviews, observations, and documentation. The results show that the planning of differentiated learning involves collaboration between the school principal and teachers, taking into account the interests, talents, and developmental levels of the children. The implementation of differentiated learning has been proven effective in increasing children's engagement and motivation, utilizing various teaching methods tailored to each child's learning style. Assessments are conducted continuously using anecdotal records, checklists, and work that reflect an authentic assessment approach. These findings suggest that differentiated learning not only motivates children's learning but also fosters an inclusive learning environment that supports the holistic development of young children. This research is expected to serve as a reference for the development of differentiated learning models in the context of early childhood education.